Edge Chemistry of Armchair Graphene Nanoribbons Containing Sulfur Functional Groups: Towards an Understanding of the Spin‐Dependent Electrochemistry. Issue 3 (23rd January 2020) - López‐Urías, Florentino; Fajardo‐Díaz, Juan L.; Cortés‐López, Alejandro J.; Rodríguez‐Corvera, Cristina L.; Jiménez‐Ramírez, Luis E.; Muñoz‐Sandoval, Emilio
Abstract: Numerous sulfur functional groups (35) attached to the edges of armchair graphene nanoribbons are investigated through the use of quantum mechanical calculations. Results for the band structure, formation energy, charge transfer, total hydrophilicity index, and electronic bandgaps are shown. The thiophene‐like functional group proved to be the most energetically stable, followed by the pyrrolic‐ N ‐sulfide. Typically, the sulfurized functional groups pulled out electrons from the ribbon, promoting p‐type doping. Ferromagnetic semiconducting behavior is found in thioketone, pyrrolic‐ N ‐sulfide, thiopyran‐like dioxide, and N ‐thionyl aniline functional groups. Results for the valence band maximum and conduction band minimum energies demonstrate that thiopyran‐like dioxide is energetically favorable to remove spin‐down electrons, whereas thioketone is energetically favorable to catch spin‐down electrons. This fact gives insight into future spin‐dependent electrochemistry studies on functionalized graphite materials. Results for lithium adsorption demonstrate that the donated charge by lithium and interatomic distance between Li and the functional groups are strongly dependent on the nature of the functional group. Abstract : More than 35 sulfur functional groups attached to the edges of armchair graphene nanoribbons are explored. Based on first‐principles density functional theory calculations, the band structure, global hydrophilicity index, charge transfer, formation energy, oxidation and reduction energies, and bandgaps of these structures are analyzed. This investigation provides valuable information to understand the edge chemistry of graphite materials.